Immediate Analgesic Efficacy of Acupuncture in Acute Postoperative Pain Following Internal Fixation of Intertrochanteric Femoral Fractures: Protocol for a Randomized Controlled Trial - Wang H; Wang T; Tang X; Tang X; Li C; Deng Y; Li Q; Liang F; Liao J; Guo T (Journal of Pain Research)
Hongyang Wang,1,* Tao Wang,2,* Xiaoxia Tang,2 Xin Tang,1 Chunxiang Li,2 Yuanzheng Deng,1 Qifu Li,3 Fanrong Liang,3 Jianglong Liao,2 Taipin Guo1 1School of Second Clinical Medicine, Yunnan University of Chinese Medicine, Kunming, People’s Republic of China; 2Kunming Municipal Hospital of Traditional Chinese Medicine, Kunming, People’s Republic of China; 3College of Acupuncture and Tuina, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianglong Liao, Kunming Municipal Hospital of Traditional Chinese Medicine, Kunming, People’s Republic of China, Email 373772123@qq.com Taipin Guo, School of Second Clinical Medicine, Yunnan University of Chinese Medicine, Kunming, People’s Republic of China, Email gtphncs@126.comPurpose: Intertrochanteric femur fractures (IFF) undergoing internal fixation often present with persistent, intolerable hip pain after surgery. Therefore, the immediate alleviation of pain constitutes a critical clinical necessity for participants. This study aims to evaluate the immediate analgesic efficacy of acupuncture within 10 minutes of treatment in participants experiencing acute postoperative pain following internal fixation of IFF.Participants and Methods: From March 2025 to March 2027, 154 postoperative IFF patients (aged 50– 75) at Kunming Municipal Hospital of Traditional Chinese Medicine will be randomized (1:1) into acupuncture or sham acupuncture groups using computer-generated randomization sequences, with allocation concealment ensured through opaque sealed envelopes. Each group will receive a 10-minute treatment session, and the post-treatment evaluation will be performed after 2, 4, 6, 8, and 10 minutes of acupuncture. The primary outcome will be pain intensity measured by the Visual Analogue Scale (VAS) at 10 minutes post-treatment. Secondary outcomes include the pain VAS score at 2, 4, 6, and 8 minutes post-treatment, the blinding assessment, and the treatment effectiveness expectations scale. This analysis will follow the intention-to-treat (ITT) principle.Discussion: This study is the first randomized controlled clinical trial to assess the immediate analgesic effects of acupuncture in participants experiencing acute postoperative pain following internal fixation for IFF. This study aims to provide a simple, rapid, and effective therapeutic option for clinical pain management after internal fixation for IFF.Keywords: intertrochanteric femoral fracture, internal fixation, immediate efficacy, acupuncture, protocol